Análise da qualidade e da acessibilidade das calçadas no entorno de parques urbanos da cidade de São Paulo/SP - Brasil - Cruz, Cristina Siqueira (2023)
This dissertation addresses the importance of urban parks for the environment and human well-being, highlighting that adequate access to these spaces is essential to ensure their benefits. In São Paulo, walking is one of the most commonly used modes of transportation, with sidewalks being fundamental to ensure accessibility to parks. However, studies indicate that the quality of sidewalks in the city is poor, especially in vulnerable areas, which can lead to risks for pedestrians and hinder the access of people with disabilities to parks. The analysis of the quality and accessibility of sidewalks around parks is crucial for the creation of more just and accessible public policies. Objective: To analyze the quality and accessibility of sidewalks around urban parks in the city of São Paulo/SP, Brazil. Method: This is an exploratory, descriptive, and quantitative study. The technical procedures involved literature review, document analysis, use of geotechnologies, and field activities. Based on the Social Vulnerability Index map of São Paulo (IPVS), two parks were selected for the diagnosis of the sidewalks around them, namely Jardim da Conquista Park and Povo Mario Pimenta Camargo Park, located in areas of High Social Vulnerability and Very Low Social Vulnerability, respectively. For the diagnoses of sidewalk conditions and crossings carried out in fieldwork, routes were established for each of the parks, aiming at the path between their entrances and the nearest bus stops or train/subway stations. Thus, for Povo Park, four routes were carried out, containing a total of 31 sections and 4 crossings, and for Jardim da Conquista Park, three routes were carried out, containing a total of 23 sections and 2 crossings. The diagnosis was then carried out using the Sidewalk Quality and Accessibility Indexes. Results: The results indicate that in Povo Park, some areas presented significant problems regarding security and maintenance, especially in the first trail, which can hinder accessibility, but the other trails presented higher security indexes. In Jardim da Conquista Park, significant problems were found in terms of security, maintenance, and sidewalk width, with conflicts between pedestrians and vehicles, sidewalks in poor conditions, lack of adequate sidewalk areas, and inadequate effective widths. Conclusion: The applied methodology can be considered a useful tool to identify problems and define necessary actions to improve the conditions of the sidewalks, which can contribute to the implementation of improvements that contribute to a safe and accessible environment. In addition, the results support studies that point to the worst accessibility conditions on sidewalks located in areas of greater social vulnerability.